Relationship Between Knowledge And Behavior Of Vulva Hygiene When Menstruate With The Event Of Pruritus Vulvae In Adolescents - Anna Hubaedah (Fakultas Ilmu Kesehatan, 2020)
ABSTRACT Pruritus vulvae is a disorder characterized by itching in the external genitals of women. Pruritus vulvae can be caused by bacteria, fungi, and viruses. The purpose of this study is to determine the relationship between knowledge and behavior about menstrual vulva hygiene with the incidence of pruritus vulvae in adolescent girls. This research uses an observational research method with a cross-sectional approach. The population is all seventh-grade female teenagers at SMP Negeri 1 Sepulu Bangkalan with 98 people. Samples were obtained by 79 people who were determined by a simple random sampling technique. The measuring instrument used was a questionnaire. Statistical tests using Lambda ρ ≤ 0.05. The results showed that there was a relationship between knowledge about vulva hygiene (p = 0.028 <α = 0.05) and behavior about vulva hygiene (p = 0.006 <α = 0.05) when menstruating with the incidence of vulvar pruritus in young women. For this reason, vulva hygiene behavior in young women must be improved because good vulva hygiene behavior will reduce the incidence of pruritus vulvae. keyword: Knowledge, Behavior, Hygiene Vulva, Menstruation, Pruritus vulvae